Assessing the Impact of Social Media Usage and Performance of the Selected Small and Medium Businesses in Ntungamo District. - Nyamwija, Bonitah (Kabale University, 2024)
The study assessed the impact of social media usage and performance of the selected small and medium businesses in the Ntungamo district. The study was guided by the following objectives; to evaluate whether small business‟ owner-managers” in the Ntungamo district find any importance of social media in their businesses, to determine the performance of small businesses in the Ntungamo district after adaptation of social media compared to the one without social media and to find the challenges encountered when small business owner-managers in Ntungamo district use social media in their business in Ntungamo district The study adopted a descriptive research design comprising of both qualitative and quantitative approaches. The study included different retail shop owners such as; clothing, cosmetics, electronic accessories, make-up services, home appliances, and food stuffs. Furthermore, some other members that added to the population were the customers who engaged in business exchange with the small businesses through social media. The researcher used a sample size of 30 respondents. The study was based on questionnaires and interviews. The collected data was analyzed manually using tallies and the responses of the subjects were then categorized in frequency counts and score tables with varying percentages calculated and later tabulation method was used to present data. The present study examined the impact of social media usage and performance of the selected small and medium businesses in Ntungamo district as a case study. The study revealed several importance of social media in their respective businesses which included; brand awareness and visibility, customer engagement and relationship building, targeted marketing and advertising, content distribution and promotion, and reputation Management. The study further revealed the impact of social media on the performance of small-scale and medium businesses which the effects included; increased brand awareness, customer engagement and relationship building, opportunities for collaboration and partnerships, targeted marketing and advertising, and cost-effective marketing channels in the Ntungamo district. The study findings further assessed the challenges encountered when small business owner-managers in the Ntungamo district use social media in their business and these included time constraints, limited expertise, Negative feedback and online reputation management, and keeping up with algorithm changes. Based on the challenges, the study findings further examined the solutions to the challenges and these were; Monitoring social media channels regularly and responding promptly and professionally to customer feedback, whether positive or negative, Investing in social media training,g and Prioritizing social media management in the study area.